Detecting malaysian jurnal of real estateand mapping nutrients concentration in oil palm plantation using remote sensing and geographic information system - Ibrahim, Abd. Latif; Hashim, Mazlan; Ali, Mohamad Idris; Rasib, Abd. Wahid; Wan Kadir, Wan Hazli; Sumari, Mohd. Razif; Haron, Khalid (2003)
Nutrient concentration in the soil is one of the major factors that determined the performance of oil palm crop growth. Shortages of nutrients are normally overcome through the application of chemical fertilizers. High cost of chemical fertilizers had contributed to high production cost. Efficient and proper management in term of fertilizer application is therefore a necessary measure to ensure better returns. Complete and detailed information regarding soil condition across the oil palm plantation is greatly required for aiding farm managers and operators in day-to-day management decision. The main focus of this paper is to examine the ability of remote sensing technique in detecting and quantifying the foliar nutrient in the oil palm crop. Results of this study that have been carried out in the Malaysian Palm Oil Board (MPOB) Research Station in Kluang, Johore showed a strong relationship between measured foliar nutrient and the spectral reflectance measured using spectroradiometer at micro level, which can in turn be regressed at macro-level with appropriate satellite data to map nutrient status for large areal extent.